Methods and means for detecting defects in the design of object-oriented software - Нечай, О.С.; Сидоров, М.О. (Proceedings of National Aviation University, 2009)
Software perfective maintenance needs design flaw identification techniques and tools. In the paper the notion of design flaw and its progress degree are introduced. Reasons of design flaw appearance and progress are defined. Also design flaw classification is developed. Paper presents analysis and classification of existing design flaw diagnostics methods and tools and ways of its further improvements.